A groundwater flow model for the Wolin Island area, including glaciotectonic deformation - Hoc, Ryszard; Sadurski, Andrzej; Wiśniowski, Zenon (Geologos, 2018)
During the construction of mathematical models for mapping hydrogeological conditions it is necessary to apply simplifications, both in the geological structure and in hydrogeological parameters used. The present note discusses problems surrounding the mapping of glaciotectonic disturbances that occur in the northern part of Wolin Island (northwest Poland). For this part of the island, a direct outflow of groundwater towards the Baltic Sea basin has been determined on the basis of geophysical survey results. An important feature in the hydrogeological conditions here is the isolation of groundwater from both the Baltic Sea and Szczecin Lagoon by clay with a Cretaceous xenolith. Such a geological structure explains the presence of perched water at considerable heights in zones close to the cliffs, without any significant hydraulic connection with surrounding reservoirs. Hydrogeological conditions of Wolin Island have been modelled using the Visual MODFLOW package v.4.2. In the vertical section, these conditions can be simplified to one aquifer (Pleistocene-Holocene), in which two aquifers can be distinguished. In a large part of the island, these remain in mutual hydraulic contact: layer I – upper, with an unconfined aquifer, and layer II – lower, with a confined aquifer, locally an unconfined one. The schematisation of hydrogeological conditions adopted here has allowed to reproduce present groundwater dynamics in the study area.